(untitled) (Research, Society and Development, 2021)
Objective: To analyze the scientific production of the last ten years, regarding the physiotherapeutic activity in the immediate puerperium and the evidence of this practice. Methods: Exploratory research of the bibliometric type, carried out through a literature review in PubMed/Medline, Web of Science, Scopus, PEDro and LILACS databases, on the physiotherapeutic performance in the immediate puerperium published in the last decade. The following descriptors were used: “postpartum”; “puerperium” and “physiotherapy”. Results: Of 814 publications, only 17 were analyzed after exclusion of certain productions according to previously defined criteria. Prevailed the quantitative studies in English, carried out in Brazil, published in the last 5 years in journals with a low SJR impact factor, which addressed the themes of evaluation and treatment of rectus abdominis diastasis (RAD), followed by the use of transcutaneos electrostimulation (TENS) for immediate postpartum pain relief and pelvic floor musculature training (PFM). Conclusion: The scientific evidence pointed as the main physiotherapeutic interventions used in the immediate puerperium exercises for RAD, PFM and TENS, but the studies present low methodological rigor and were published in periodicals with low impact factor. It is suggested that new studies with greater methodological rigor be carried out only for women in the immediate puerperium to produce scientific evidence of better quality.